Evaluating the expression level of genes related to autophagy in rheumatoid arthritis patients: Genes related to autophagy in rheumatoid arthritis - Zhao, Wen; Shi, Shengbin; Jian, Ai; Wang, Yiqi; Zhao, Qianqian (Cellular and Molecular Biology, 2023)
Rheumatoid arthritis or joint rheumatism is the most common systemic inflammatory disease of the joints and is considered one of the chronic autoimmune diseases. T cells and other immune cells are called to the synovial tissue and cause this disease to progress. Autophagy is a process that is associated with the breakdown of intracellular organelles. As a regulator of cell homeostasis, it can affect the activation of immune cells and participate in the pathogenesis of rheumatoid arthritis. This study aimed to evaluate the gene expression level of autophagy genes in two groups of rheumatoid arthritis patients and healthy individuals. For this purpose, peripheral blood was obtained from two groups of people, including 40 rheumatoid arthritis patients, and 40 healthy individuals. The expression of two genes related to autophagy, Atg5, and Beclin-1, was evaluated in peripheral blood cells using the real-time PCR method. The results showed that the expression of the Beclin-1 gene increased by 2.21 times in rheumatoid arthritis patients compared to healthy individuals (P = 0.024). The expression of the Atg5 gene in rheumatoid arthritis patients increased by 1.53 times compared to healthy subjects (P = 0.041). In general, this study showed that in rheumatoid arthritis patients, increased expression of autophagy genes could be involved in the pathogenesis of this disease. In other words, the findings showed that reducing autophagy can reduce the severity of the disease in people with rheumatoid arthritis.